Behavioral Finance and Investor Types: Managing Behavior to Make Better Investment Decisions - Michael M. Pompiam
Introduction to Behavioral Finance: Why Reaching Financial Goals Is Difficult, Overview of Behavioral Finance, Overview of Behavioral Finance; Personality Theory: Introduction to Personality Theory, The History of Personality Testing, The Behavioral Investor Type Framework, Behavioral Investor Type Diagnostic Testing; Three Explanation of the Behavioral Investor Types: The Preserver, The Follower, The Independent, The Accumulator; Plan and Act: Capital Markets and Asset Classes, What Is Asset Allocation?, Financial Planning: A Crucial Step